2019
DOI: 10.1097/mpa.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Pancreastatin Predicts the Outcome of Surgical Cytoreduction in Neuroendocrine Tumors of the Small Bowel

Abstract: Objectives Elevated pancreastatin (PST) levels have been shown to be associated with poor prognosis in small bowel neuroendocrine tumors (NETs). We hypothesized that plasma PST levels that remain elevated following surgical cytoreduction portend a poor prognosis in well-differentiated small bowel NETs. Methods Patients diagnosed with small bowel NETs who underwent surgical cytoreduction at our institution were identified. Demographics, histopathologic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…In addition, Woltering et al studied pre and post-operative levels of pancreastatin in 300 patients with SI-NETs who underwent surgical cytoreduction. Authors found that patient who had normal pancreastatin after surgery had significantly better 5and 10-year survival rates compared to patients in whom pancreastatin remained elevated postoperatively (p < 0.0001) [37]. Similar findings were also reported by Sherman et al where higher pancreastatin levels were associated with worse PFS and OS in patients with SI-NETs [38].…”
Section: Pancreastatinsupporting
confidence: 60%
“…In addition, Woltering et al studied pre and post-operative levels of pancreastatin in 300 patients with SI-NETs who underwent surgical cytoreduction. Authors found that patient who had normal pancreastatin after surgery had significantly better 5and 10-year survival rates compared to patients in whom pancreastatin remained elevated postoperatively (p < 0.0001) [37]. Similar findings were also reported by Sherman et al where higher pancreastatin levels were associated with worse PFS and OS in patients with SI-NETs [38].…”
Section: Pancreastatinsupporting
confidence: 60%